2016
DOI: 10.4134/bkms.b150337
|View full text |Cite
|
Sign up to set email alerts
|

STABILITY OF MAP/PH/c/K QUEUE WITH CUSTOMER RETRIALS AND SERVER VACATIONS

Abstract: Abstract. We consider the M AP/P H/c/K queue in which blocked customers retry to get service and servers may take vacations. The time interval between retrials and vacation times are of phase type (PH) distributions. Using the method of mean drift, a sufficient condition of ergodicity is provided. A condition for the system to be unstable is also given by the stochastic comparison method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Breuer et al [9] indicate that the proof of the sufficient condition for K = c is not correct. However, Shin [49] showed that the result of [25] is correct . Approximation methods for the system with non-exponential retrial times are developed for M/G/1 retrial queue with general retrial time [67], for M/G/1 retrial queue with mixture of Erlang retrial time [35] and for M/P H/1 retrial queue with P H-retrial time [15].…”
Section: Bibliographical Notesmentioning
confidence: 99%
See 3 more Smart Citations
“…Breuer et al [9] indicate that the proof of the sufficient condition for K = c is not correct. However, Shin [49] showed that the result of [25] is correct . Approximation methods for the system with non-exponential retrial times are developed for M/G/1 retrial queue with general retrial time [67], for M/G/1 retrial queue with mixture of Erlang retrial time [35] and for M/P H/1 retrial queue with P H-retrial time [15].…”
Section: Bibliographical Notesmentioning
confidence: 99%
“…) is a continuous time Markov chain on the state space S = {(n n n, k, j) ∈ Z g+2 + : n n n ≥ 0, 0 ≤ k ≤ c, 0 ≤ j ≤ w} and Ψ Ψ Ψ is positive recurrent if ρ = λ cµ < 1 [49]. Let (X X X, Y, J) be the stationary version of Ψ Ψ Ψ.…”
Section: Bibliographical Notesmentioning
confidence: 99%
See 2 more Smart Citations
“…The stability condition of our multiserver retrial queue is a new finding in the sense that it is different from that of the corresponding queue without retrials. In this line, we recently became aware of Shin [24] in which a stability condition is derived for MAP/PH/c/K retrial queues with vacation. It should be noted that vacation model is essentially different from setup model because in the former a vacation is independent of waiting customers while in the latter OFF servers are activated by waiting jobs.…”
Section: Tuan Phung-duc and Ken'ichi Kawanishimentioning
confidence: 99%